Formulation and release testing of mecobalamin in gelatin capsule derived from striped Snakehead (Channa striata) - Sari, Mayang; Diana, Vivi Eulis; Siahaan, Azmialamsyah Putra (Pharmaciana, 2025)
Capsules are medicinal preparations wrapped in hard or soft capsule shells. The material for making capsule shells is gelatin obtained from partial hydrolysis of animal skin or bones. One source of gelatin that can be used as a basic material for forming capsule shells is snakehead fish skin. This study aimed to produce capsule shells from snakehead skin, varying the gelatin concentration in the capsule shells, and to assess the drug release properties. The evaluation of the capsule shells included measurements of length, diameter, thickness, weight, volume, disintegration time, swelling degree, and mecobalamin release using a dissolution apparatus in a simulated gastric fluid medium, with mecobalamin levels measured by UV spectrophotometry. The results showed that the snakehead capsule displayed good physical properties. The best swelling degree was observed in formula 2, with a value of 24.59%, which is close to the 27.58% swelling degree of commercial capsules (mecobalamin) at the 10-min. The mecobalamin release test indicated that the capsules from formula 2 released 30.40% of the drug at the 30-min when tested at 278 nm, compared to 33.50% from commercial capsules. Testing at a wavelength of 352 nm for formula 2 was 29.25% compared to commercial mecobalamin capsules at 34.67%. These findings highlight the promising utility of gelatin from snakehead skin in the formulation of effective drug delivery systems.